THE EFFECT OF KNOWLEDGE SHARING AND LEADER-MEMBER EXCHANGE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS A MEDIATION VARIABLE (STUDY ON GUDEG YU DJUM PUSAT YOGYAKARTA) - Ragil Listyowati; Syamsul Hadi; Epsilandri Septyarini (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of Knowledge Sharing and Leader Member Exchange on employee performance with Organizational Citizenship Behavior (OCB) as a mediating variable at Gudeg Yu Djum Pusat. This research employs a quantitative approach with a descriptive method. Data was collected through questionnaires distributed to 80 employees selected using purposive sampling. The results indicate that Knowledge Sharing has a positive effect on OCB, Leader Member Exchange also positively influences OCB, and OCB positively affects employee performance. Additionally, OCB acts as a mediating variable in the relationship between Knowledge Sharing and performance, as well as between Leader Member Exchange and performance. This study contributes both theoretically and practically to the human resource management of Gudeg Yu Djum Pusat by enhancing performance through improved Knowledge Sharing, quality relationships between leaders and employees, and behaviors that support operational efficiency.